2017
DOI: 10.1111/ele.12831
|View full text |Cite
|
Sign up to set email alerts
|

No consistent pollinator‐mediated impacts of alien plants on natives

Abstract: The introduction of an alien plant is widely assumed to have negative consequences for the pollinator-mediated fitness of nearby natives. Indeed, a number of studies, including a highly cited meta-analysis, have concluded that the trend for such interactions is competitive. Here we provide evidence that publication bias and study design have obscured our ability to assess the pollinatormediated impacts of alien plants. In a meta-analysis of 76 studies, we demonstrate that alien/ native status does not predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 91 publications
(211 reference statements)
1
62
1
Order By: Relevance
“…). For example, a recent meta‐analysis found that presence of co‐flowering plants does not significantly reduce seed and fruit production (Charlebois and Sargent ), suggesting that manipulating co‐flowering plants should have a relatively small effect on selection on floral traits (e.g., Wassink and Caruso ). Alternatively, other biotic factors could have a relatively small effect on selection because variation in floral traits has a weaker effect on the probability of antagonistic and/or competitive interactions than on pollination (e.g., Sandring and Ågren ).…”
Section: Discussionmentioning
confidence: 99%
“…). For example, a recent meta‐analysis found that presence of co‐flowering plants does not significantly reduce seed and fruit production (Charlebois and Sargent ), suggesting that manipulating co‐flowering plants should have a relatively small effect on selection on floral traits (e.g., Wassink and Caruso ). Alternatively, other biotic factors could have a relatively small effect on selection because variation in floral traits has a weaker effect on the probability of antagonistic and/or competitive interactions than on pollination (e.g., Sandring and Ågren ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is growing evidence (and concerns) that invasive mutualists may competitively displace native mutualists (e.g., Grove et al. , but see Charlebois and Sargent ). Yet, while it is widely recognized that species compete for commodities, the consistency and strength of competition are rarely measured (Jones et al.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been little support for a consistent effect of species invasions on pollinator visitation network structure (Vil a et al, 2009;Albrecht et al, 2014). A recent meta-analysis (Charlebois & Sargent, 2017) found no consistent effects of invasive plant species' presence on visitation and seed set in coflowering native species. There is reason to predict, however, that in some cases, introduced species have strong impacts on pollen transfer dynamics and native species reproductive fitness.…”
Section: Introductionmentioning
confidence: 99%